A computational and empirical perspective on gendered correlates of heterogeneous childlessness: Micro-level inequalities, meso-level networks and macro-level developments - Verkroost, FCJ (2023)
This thesis investigates childlessness across time and levels of socio-economic development as well as its pathways and consequences in individual life courses, and the role social network influences play in connecting the two. Throughout three standalone but related papers, this thesis first examines the gendered relationship between childlessness types and development components in sub-Saharan African subnational regions using hierarchical modelling and Demographic and Health Surveys data. Second, it proposes a Bayesian hierarchical growth curve modelling approach, using 1970 British Cohort Study data, to assess the accumulation of socio-economic (dis)advantage throughout the life courses of parents and permanently childless men and women. Third, it investigates the role of structural and compositional characteristics of social networks in the interaction between individual-level childbearing behaviour and aggregate childlessness patterns using agent-based simulation models calibrated to Dutch data and emulated by statistical and machine learning models. This thesis contributes to the literature by examining childlessness from the interconnected micro-, meso-, and macro-level perspectives; acknowledging the heterogeneity regarding gender and reasons for childlessness; and applying advanced methodologies to overcome current modelling limitations. The findings suggest that in developing regions, macro-level decreases in involuntary childlessness and increases in voluntary and circumstantial childlessness may be explained by educational, income and health advancements. In developed regions, remaining childless may contribute to the accumulation of socio-economic (dis)advantage throughout individuals’ life courses. Decreasing abidance to social norms through increasingly individualistic meso-level social networks may connect macro-level childlessness norms and patterns which emerge from and sequentially influence micro-level childbearing values and behaviours. Contextual factors on the micro-, meso- and macro-levels, such as marriage and employment, influence the direction and magnitude of the observed associations. The findings have societal and policy implications regarding the viability of populations and welfare states; equality by both parental status and gender; and public perceptions of childlessness.